Copolymerized polyester resin

By controlling the content of cyclic monomers and trimers in copolyester resins and adjusting the catalyst combination, the problems of mold contamination and resin coloring in PET production are solved, the transparency and reuse of the product are improved, and high quality is achieved polyester resin production.

CN119137184APending Publication Date: 2024-12-13TOYOBO MC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380035422.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-22
Filing Date
2023-03-28
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When producing polyethylene terephthalate (PET), the problems of mold contamination, foreign matter adhesion, resin coloration, and molecular weight reduction generated in the copolyester resin affect the transparency and reuseability of the product.

Method used

By controlling the content of cyclic monomers and cyclic trimers in the copolyester resin, adjusting the carboxyl terminal concentration and using a specific catalyst combination, optimizing the ratio of diethylene glycol and sodium sulfoisophthalate to ensure the heat of the resin Stability and moldability.

Benefits of technology

Effectively prevent mold contamination, foreign matter adhesion and resin coloring, improve product transparency and reuse, and ensure high quality and value of resin in production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005094328620000111
    Figure BDA0005094328620000111
  • Figure BDA0005094328620000121
    Figure BDA0005094328620000121
  • Figure BDA0005094328620000122
    Figure BDA0005094328620000122
Patent Text Reader

Abstract

The present invention addresses the problems of mold contamination and foreign matter adhesion to a product when continuously producing a film, molded article, fiber or other products in a copolymerized polyester resin obtained by copolymerizing diethylene glycol and sodium sulfoisophthalate, and the problems of resin coloring and molecular weight reduction when reutilized. A copolymerized polyester resin containing terephthalic acid as a main component of a dicarboxylic acid component and ethylene glycol as a main component of a diol component, the copolymerized polyester resin being characterized in that the ratio of the terephthalic acid component to the total dicarboxylic acid component is 70-99.95 mol%, and the ratio of the ethylene glycol component to the total dicarboxylic acid component is 70-99.95 mol%, with respect to the total amount of the dicarboxylic acid component being 100 mol%, in the total polyester resin component. The ratio of the sodium sulfoisophthalate to the total dicarboxylic acid component is 0.05-10 mol%, the ratio of the diethylene glycol to the total diol component is 1-10 mol% when the total amount of the diol component is 100 mol%, and the content of free cyclic monomers comprising terephthalic acid, sodium sulfoisophthalate, ethylene glycol, and diethylene glycol is 20 ppm or less. And the content of free cyclic trimers comprising terephthalic acid, sodium sulfoisophthalate, and ethylene glycol is 200 ppm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copolymerized polyester resin which is excellent in transparency and moldability, hardly causes contamination around the mold and foreign matter adhesion during the production of products such as films, and has excellent recyclability. Background Art

[0002] Polyethylene terephthalate (PET), which is produced from polyester, especially terephthalic acid (hereinafter sometimes referred to as TPA) and ethylene glycol (hereinafter sometimes referred to as EG) as raw materials, is widely used in containers, films, sheets, fibers, etc. due to its excellent chemical and physical properties.

[0003] In recent years, among polyethylene terephthalate (PET), polyester resins (hereinafter sometimes referred to as copolyester resins) obtained by copolymerizing diethylene glycol (hereinafter sometimes referred to as DEG) have attracted attention due to their excellent transparency, moldability, impact resistance, heat resistance, etc., and have been used for various purposes, especially as raw material polymers for molded bodies such as films, sheets, injection molded bodies, and heteromorphic molded bodies.

[0004] In addition, polyester resins obtained by copolymerizing sodium sulfoisophthalate (hereinafter, sometimes abbreviated to GCM) (hereinafter, sometimes abbreviated to copolyester resin) have attracted attention due to their excellent biodegradability and have been used for various purposes, particularly as base polymers for molded products such as films, sheets, injection molded products, and heteromorphic molded products (see Patent Documents 1 to 6).

[0005] However, when the copolyester resins produced by the techniques of Patent Documents 1 to 6 are used to continuously produce products such as films, molded articles, and fibers, there is a problem that low-melting-point foreign matter adheres to the mold or near the die, and the foreign matter is transferred and adheres to the surface of the product, thereby reducing the product value. In addition, there is a problem that the resin is colored and the molecular weight is reduced when it is reused. Prior art literature Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2010-150542 Patent Document 2: Japanese Patent No. 4755995 Patent Document 3: Japanese Patent No. 4614963 Patent Document 4: Japanese Patent Application No. 2007-500769 Patent Document 5: Japanese Patent No. 4807952 Patent Document 6: Japanese Patent No. 5345749 Summary of the invention Problems to be solved by the invention

[0007] The present invention is invented to solve the above-mentioned problems of the prior art, and solves the following problems: in the copolymerized polyester resin obtained by copolymerizing diethylene glycol and sodium sulfoisophthalate in order to improve transparency and moldability, there are problems of mold contamination and foreign matter adhesion to the product when continuously producing products such as films, molded products, and fibers, and there are problems of resin coloration and molecular weight reduction when recycled. Means of solving problems

[0008] In order to solve the above problems, the present inventors conducted in-depth research on the causes of mold contamination and foreign matter adhesion to products in copolyester resins obtained by copolymerizing diethylene glycol and sodium sulfoisophthalate. As a result, it was found that specific cyclic monomers and cyclic trimers (hereinafter sometimes referred to as cyclic oligomers) generated as by-products during the production of copolyester resins are the causes of mold contamination and foreign matter adhesion to products. By suppressing the content of these by-products to a certain value or less, a copolyester resin with almost no problems of mold contamination and foreign matter adhesion to products can be provided. In addition, the inventors conducted in-depth research on the causes of coloration and molecular weight reduction of resins during recycling. As a result, it was found that diethylene glycol and sodium sulfoisophthalate used as materials for copolyester resins improve transparency and moldability while reducing the thermal stability and thermal oxidation stability of the obtained copolyester resin. Therefore, it is believed that the resin deteriorates due to heating during film formation and during the production of molded products, and the film and molded products are colored and their molecular weight is reduced. Then, the present inventors studied methods for improving the thermal stability and thermal oxidation stability of the copolyester resin and found that it is important to control the carboxyl terminal group concentration (AV) of the copolyester resin within a certain range and to use a specific combination of two catalysts used in polymerization, thereby completing the present invention.

[0009] That is, the present invention has been accomplished based on the above-mentioned findings and has the following structures (1) to (12). (1) A copolyester resin characterized in that it is a copolyester resin containing terephthalic acid as a main dicarboxylic acid component and ethylene glycol as a main diol component, wherein, in all polyester resin components, when the total amount of dicarboxylic acid components is 100 mol%, the ratio of terephthalic acid components to all dicarboxylic acid components is 70 to 99.95 mol%, the ratio of sodium sulfoisophthalate to all dicarboxylic acid components is 0.05 to 10 mol%, the ratio of diethylene glycol to all diol components is 1 to 10 mol%, the content of free cyclic monomers consisting of terephthalic acid, sodium sulfoisophthalate, ethylene glycol and diethylene glycol is 20 ppm or less, and the content of free cyclic trimers consisting of terephthalic acid, sodium sulfoisophthalate and ethylene glycol is 200 ppm or less. (2) The copolyester resin according to (1), characterized in that the color b value is -5.0 to 15.0. (3) The copolyester resin according to (1), wherein the carboxyl terminal group concentration (AV) is 3 to 25 eq / t. (4) The copolyester resin according to (1), characterized in that the copolyester resin contains aluminum atoms and phosphorus atoms, the content of aluminum atoms in the copolyester resin is 15 to 40 ppm, and the molar ratio of phosphorus atoms to aluminum atoms in the copolyester resin is greater than 0 and less than 2.6. (5) The copolyester resin according to (1), characterized in that the copolyester resin further contains alkali metal atoms and / or alkaline earth metal atoms derived from alkali metal compounds and / or alkaline earth metal compounds other than sodium sulfoisophthalate, and the content of the alkali metal atoms and / or alkaline earth metal atoms in the copolyester resin is 1 to 100 ppm. (6) The copolyester resin according to any one of (1) to (5), wherein a step-shaped molded plate obtained by molding the copolyester resin has a haze value of 10% or less at a thickness of 5 mm. (7) A molded article comprising the copolyester resin according to any one of (1) to (5). (8) A heat shrinkable film comprising the copolyester resin according to any one of (1) to (5). (9) A fiber characterized by comprising the copolyester resin according to any one of (1) to (5). (10) A nonwoven fabric comprising the copolyester resin according to any one of (1) to (5). (11) An adhesive comprising the copolyester resin according to any one of (1) to (5). (12) A coating material comprising the copolyester resin according to any one of (1) to (5). Effects of the Invention

[0010] The copolymerized polyester resin of the present invention has the advantages of transparency and moldability due to the use of diethylene glycol and sodium sulfoisophthalate, and in the case of continuous production of films, molded articles, fibers and other products, there is almost no mold contamination or foreign matter attached to the product, and there is no coloring of the resin or reduction in molecular weight during recycling. DETAILED DESCRIPTION

[0011] Hereinafter, the copolyester resin of the present invention will be described in detail. In the copolyester resin of the present invention containing terephthalic acid as the main component of the dicarboxylic acid component and ethylene glycol as the main component of the diol component, diethylene glycol and sodium sulfoisophthalate are copolymerized for the sake of transparency and moldability. The copolyester resin has the following characteristics: by suppressing the content of specific cyclic monomers and cyclic trimers produced as by-products during polymerization to a certain value or less, mold contamination and foreign matter adhesion to the product are effectively prevented. Furthermore, by controlling the carboxyl terminal group concentration (AV) of the copolyester resin within a certain range and using a specific combination of two catalysts used in the polymerization, the problems of resin coloration and molecular weight reduction during recycling are effectively prevented.

[0012] The copolyester resin of the present invention contains terephthalic acid as a main dicarboxylic acid component. Specifically, when the total amount of dicarboxylic acid components is 100 mol %, the ratio of terephthalic acid to the total dicarboxylic acid components is 70 to 99.95 mol %, preferably 80 to 99.95 mol %, and more preferably 90 to 99.95 mol %.

[0013] The copolyester resin of the present invention contains sodium sulfoisophthalate as a dicarboxylic acid component in addition to terephthalic acid in order to improve biodegradability. Specifically, with respect to the content of sodium sulfoisophthalate, when the total amount of dicarboxylic acid components is 100 mol%, the ratio of sodium sulfoisophthalate to the total dicarboxylic acid components is 0.05 to 10 mol%, preferably 0.1 to 5 mol%, and more preferably 0.2 to 3 mol%. When the content of sodium sulfoisophthalate is less than the above lower limit, the haze value is high and the DSC measurement tends to be poor. On the other hand, when the content of sodium sulfoisophthalate is greater than the above upper limit, the amount of the following free cyclic monomer and cyclic trimer increases, and mold contamination and foreign matter adhesion to the product increase.

[0014] The copolymerized polyester resin of the present invention may contain other dicarboxylic acid components in addition to terephthalic acid and sodium sulfoisophthalate. Examples of the other dicarboxylic acid components include (1) aromatic dicarboxylic acids such as isophthalic acid, phthalic acid, 2,6-naphthalene dicarboxylic acid, diphenyl-4,4'-dicarboxylic acid, and diphenoxyethane dicarboxylic acid, and their functional derivatives; (2) aliphatic dicarboxylic acids such as adipic acid, sebacic acid, succinic acid, glutaric acid, dimer acid, dodecanedicarboxylic acid, and azelaic acid, and their functional derivatives; (3) alicyclic dicarboxylic acids such as hexahydroterephthalic acid, hexahydroisophthalic acid, and cyclohexane dicarboxylic acid, and their functional derivatives.

[0015] The copolyester resin of the present invention contains ethylene glycol as a main component of the diol component. Specifically, when the total amount of the diol component is 100 mol%, the ratio of ethylene glycol to the total diol component is preferably 50 to 99 mol%, more preferably 70 to 99 mol%, further preferably 80 to 99 mol%, and particularly preferably 90 to 99 mol%.

[0016] The copolyester resin of the present invention contains diethylene glycol as a glycol component in addition to ethylene glycol in order to improve transparency and moldability. Specifically, when the total amount of glycol components is 100 mol%, the ratio of diethylene glycol to all glycol components is 1 to 10 mol%, preferably 2 to 9 mol%, and more preferably 3 to 8 mol%. By making the content of diethylene glycol within the above range, a highly transparent, i.e., amorphous copolyester resin can be obtained. When the content of diethylene glycol is less than the above lower limit, the transparency of the molded product and film becomes poor due to the crystalline state, and sufficient transparency cannot be achieved, and the product value tends to be lost. On the other hand, when the content of diethylene glycol is greater than the above upper limit, the amount of the following free cyclic monomer increases, and mold contamination and foreign matter adhesion to the product increase.

[0017] During the polymerization of the copolyester resin, diethylene glycol is also generated by condensation of ethylene glycol. The amount of diethylene glycol generated by this condensation varies depending on the polymerization conditions and the manufacturing equipment, but is about 0.5 to 2.0 mol% relative to the total diol components. Considering this amount, the amount of diethylene glycol added as a raw material can be considered.

[0018] In addition, the amorphous property here means that: when a sample placed at 120°C for 120 minutes in a Yamato DP63 dryer is heated from -100°C to 300°C at 20°C / min, then cooled to -100°C at 50°C / min, and then heated from -100°C to 300°C at 20°C / min, no melting peak appears in any of the heating processes using a differential scanning calorimeter (DSC). The copolyester resin of the present invention is amorphous, and thus, even a thick molded body can have transparency that can be preferably used. That is, the "amorphous property" under the present measurement conditions means that the transparency of the film can be maintained with high quality, and even a thick film can maintain sufficient transparency.

[0019] The copolymerized polyester resin of the present invention may also contain other diol components besides ethylene glycol and diethylene glycol. Examples of the other diol components include (1) aliphatic diols such as tetramethylene glycol, pentamethylene glycol, and hexamethylene glycol; (2) alicyclic diols such as 1,3-cyclohexanedimethanol and 1,4-cyclohexanedimethanol; and (3) aromatic diols such as p-phenylenedimethanol and m-phenylenedimethanol.

[0020] In the copolyester resin of the present invention, from the perspective of improving profile extrusion moldability, it is preferred to contain 0.001 to 5 mol % of a polyfunctional compound having three or more carboxyl groups, hydroxyl groups or their ester-forming groups (e.g., trimellitic acid, pyromellitic acid, glycerol, trimethylolpropane, etc.) based on the acid component and / or diol component of the copolyester resin.

[0021] The essential feature of the copolyester resin of the present invention is that the content of specific cyclic monomers and cyclic trimers generated as by-products during polymerization is suppressed to a certain value or less, thereby effectively preventing mold contamination and foreign matter adhesion to the product. Specifically, in the copolyester resin of the present invention, the content of free cyclic monomers composed of terephthalic acid, sodium sulfoisophthalate, ethylene glycol and diethylene glycol is 20 ppm or less, and the content of free cyclic trimers composed of terephthalic acid, sodium sulfoisophthalate and ethylene glycol is 200 ppm or less. In the present invention, the free cyclic monomer composed of terephthalic acid, sodium sulfoisophthalate, ethylene glycol and diethylene glycol refers to a cyclic monomer (hereinafter referred to as TESD) in which terephthalic acid, ethylene glycol, sodium sulfoisophthalate and diethylene glycol are bonded in this order to form a ring, and the cyclic trimer composed of terephthalic acid, sodium sulfoisophthalate and ethylene glycol refers to a cyclic trimer (hereinafter referred to as T2SE3) in which terephthalic acid, ethylene glycol, terephthalic acid, ethylene glycol, sodium sulfoisophthalate and ethylene glycol are bonded in this order to form a ring. In addition, in the present invention, "copolyester resin" refers not only to chemical substances called polyesters, but also includes polyesters containing oligomer components such as TESD and T2SE3 or catalyst components described later. When explaining chemical substances called polyesters, they are sometimes described as "copolyester resins" for convenience.

[0022] The content of TESD needs to be below 20ppm, preferably below 10ppm, more preferably below 5ppm. When greater than the above upper limit, the pollution near the resin outlet of the die of the extruder during film and fiber production becomes serious, and the attached foreign matter adheres to the surface of the molded body, the surface state deteriorates, and the transparency is also affected, so that the commodity value is reduced. In addition, when the molded product is continuously injection molded, the mold exhaust port of the injection molding is blocked, and it becomes impossible to obtain a normal molded product. In addition, for the economy during production, the lower limit of this content is 1ppm. The content of TESD is a quantitative value according to the determination method of the embodiment described later.

[0023] The content of T2SE3 needs to be less than 200ppm, preferably less than 150ppm, and more preferably less than 100ppm. When it is greater than the above upper limit, the pollution near the resin outlet of the die of the extruder during film and fiber production becomes serious, and the attached foreign matter adheres to the surface of the molded body, the surface state deteriorates, and the transparency is also affected, so that the commodity value tends to decrease. In addition, when the molded product is continuously injection molded, the exhaust port of the injection molding mold is blocked, and a normal molded body cannot be obtained. In addition, for the economy during production, the lower limit of the content is 1ppm. The content of T2SE3 is a quantitative value according to the determination method of the embodiment described later.

[0024] The mechanism by which T2SE3 and TESD cause contamination and foreign matter adhesion around the mold is unclear, but it is considered that due to the steric hindrance of ethylene glycol and sulfoisophthalic acid in T2SE3, the melting point and glass transition temperature of T2SE3 become lower, and further due to the steric hindrance of diethylene glycol and sulfoisophthalic acid in TESD, the melting point and glass transition temperature of TESD become lower than those of T2SE3, so strong adhesion is exhibited, and due to the synergistic effect of TESD and T2SE3, the adhesion to the mold during molding and the film extrusion molding machine increases.

[0025] In the copolyester resin of the present invention, the terminal carboxyl group concentration is preferably 3 to 25 equivalents per ton of polymer, and more preferably 5 to 23 equivalents per ton. By making the terminal carboxyl group concentration within the above range, it can help to suppress the coloring of the copolyester resin. When the coloring of the copolyester resin is allowed to be slightly poor, the terminal carboxyl group concentration may be 32 equivalents per ton or less. If productivity (reaction time) is not considered, the lower limit of the terminal carboxyl group concentration is 0 equivalents per ton.

[0026] The number average molecular weight of the copolyester resin of the present invention is preferably 2000 to 30000, more preferably 2500 to 28000, and further preferably 3000 to 27000. When the number average molecular weight is less than the above lower limit, the crystallinity increases and the haze increases. Furthermore, due to insufficient resin cohesion, the strength and elongation of the molded product may be insufficient, and the molded product may become brittle and unusable. On the other hand, when the number average molecular weight is greater than the above upper limit, the melt viscosity is too high, so the optimum temperature in various molding processes may also increase, the thermal stability may deteriorate, and the film-forming property of the sheet may decrease. Furthermore, the amount of the above TESD and T2SE3 increases, and as a result, the transparency of the molded product may deteriorate due to mold contamination and foreign matter adhesion.

[0027] The glass transition temperature of the copolyester resin of the present invention is preferably 40°C or more and less than 120°C, more preferably 45°C or more and less than 115°C, further preferably 50°C or more and less than 110°C, and particularly preferably 50°C or more and less than 70°C. The glass transition temperature here refers to a value measured by using a differential scanning calorimeter (DSC) at a temperature increase of 20°C / min. When the glass transition temperature is less than the above lower limit, when the profile extruded molded product is used outdoors in summer, or when the product is transported or stored in a closed state in summer, there is a case where the film or profile extruded molded product is thermally deformed. In addition, when the glass transition temperature is greater than the above upper limit, the film-forming property and transparency of the sheet tend to decrease, and it may not be used depending on the application.

[0028] The color b value of the copolyester resin of the present invention is preferably -5.0 to 15.0. The lower limit of the color b value is more preferably -3.0, and further preferably -2.5. In addition, the upper limit is more preferably 14.0, and further preferably 13.0. When the color b value is greater than the above upper limit, the yellowness of the copolyester resin becomes stronger, which is not preferred in terms of color tone. On the other hand, when the color b value is less than the above lower limit, the blue hue of the copolyester resin becomes obvious, and it may not be used depending on the purpose.

[0029] The step-shaped molded plate obtained by molding the copolyester resin of the present invention at a mold temperature of 10° C. preferably has a haze value of 10% or less, more preferably 9% or less, and particularly preferably 8% or less at a thickness of 5 mm. If the haze value exceeds the upper limit, the transparency of the molded article or film deteriorates, and the molded article or film may not be used in applications requiring strict transparency.

[0030] The copolyester resin of the present invention may be added with other components as appropriate according to the application. For example, impact resistance enhancers, fillers, ultraviolet absorbers, surface treatment agents, lubricants, light stabilizers, pigments, antistatic agents, antibacterial agents, crosslinking agents, sulfur antioxidants, flame retardants, plasticizers, processing aids, foaming agents, etc. may be added. The copolyester of the present invention may be appropriately molded into various molded bodies by extrusion blow molding, drawing molding, injection molding, profile extrusion molding, calendering molding, etc., which have been used in PET and the like.

[0031] The copolyester resin of the present invention can be suitably used in various applications requiring transparency, moldability, etc., and can be used as a raw material for molded products, heat shrinkable films, fibers, nonwoven fabrics, adhesives, coatings, and the like.

[0032] Next, the method for producing the copolyester resin of the present invention is described. The copolyester resin of the present invention can be produced by a production method using a direct esterification reaction and a polycondensation reaction, or a production method using an ester exchange reaction and a polycondensation reaction. The above reaction can be carried out using a continuous reaction device or a batch reaction device, but it is preferably carried out using a continuous reaction device in terms of economy and quality stability.

[0033] In the continuous reaction apparatus (continuous polycondensation method), the esterification reaction, the transesterification reaction and the melt polycondensation reaction can be carried out in one stage respectively, preferably in multiple stages. When the esterification reaction or the transesterification reaction is carried out in multiple stages, the number of reaction tanks is preferably 2 tanks to 3 tanks. In addition, when the melt polycondensation is carried out in multiple stages, the number of reaction tanks is preferably 3 tanks to 7 tanks.

[0034] When the copolyester resin of the present invention is manufactured by a continuous polycondensation method, a slurry containing 1.02 to 1.5 moles, preferably 1.03 to 1.4 moles of all diols relative to 1 mole of all dicarboxylic acids or their ester derivatives is prepared, and the slurry is continuously supplied to the esterification reaction step containing oligomers. The esterification reaction temperature is usually 240 to 270°C, preferably 250 to 265°C. In addition, the pressure in the reaction tank is usually 0.2 MPa or less, preferably 0.01 to 0.05 MPa. In addition, the temperature of the polycondensation reaction is usually 265 to 285°C, preferably 270 to 280°C, and the pressure in the reaction tank is usually 1.5 hPa or less, preferably 0.5 hPa or less. The reaction time of the esterification reaction is preferably 5 hours or less, and particularly preferably 2 to 3.5 hours. In addition, the reaction time of the polycondensation reaction is preferably 3 hours or less, and particularly preferably 1 to 2 hours.

[0035] When the copolyester resin of the present invention is manufactured by an intermittent polycondensation method, the esterification reaction temperature is usually 220 to 250°C, preferably 230 to 245°C. In addition, the pressure in the reaction tank is usually 0.2 to 0.4 MPa, preferably 0.25 to 0.30 MPa. In addition, the polycondensation reaction can be carried out in one stage or in multiple stages. When it is carried out in one stage, the pressure is gradually reduced and the temperature is increased, and the final temperature is set to 260 to 280°C, preferably in the range of 265 to 275°C, and the final pressure is usually set to less than 3 hPa, preferably less than 0.5 hPa. The reaction time of the esterification reaction is preferably less than 4 hours, and particularly preferably 2 to 3 hours. In addition, the reaction time of the polycondensation reaction is preferably less than 5 hours, and particularly preferably 1 to 3 hours.

[0036] Then, when manufacturing the oligocondensate by continuous transesterification reaction, a solution containing dimethyl terephthalate and diol is prepared, wherein the diol is 1.1 to 1.6 mol, preferably 1.2 to 1.5 mol, relative to 1 mol of dimethyl terephthalate, and the solution is continuously supplied to the transesterification reaction step. The transesterification reaction temperature is usually 200 to 270°C, preferably 230 to 265°C. In the case of the transesterification method, in addition to the polycondensation catalyst, it is also necessary to use an transesterification catalyst. The obtained oligocondensate is reacted in the same manner as the above-mentioned continuous polycondensation.

[0037] When producing a low polycondensate by a batch transesterification reaction, dimethyl terephthalate and a diol are added to a batch reactor, wherein the diol is 2.3 to 2.0 mol, preferably 2.2 to 2.0 mol, per 1 mol of dimethyl terephthalate, and the reaction is carried out in the presence of a transesterification catalyst. The obtained low polycondensate is polycondensed in the same manner as in the above-mentioned esterification reaction.

[0038] As the polycondensation catalyst, at least one of an antimony compound, a germanium compound, a titanium compound, and an aluminum compound can be used. Examples of the antimony compound include antimony trioxide, antimony pentoxide, antimony acetate, and antimony glycol. Among them, antimony trioxide, antimony acetate, and antimony glycol are preferred, and antimony trioxide is particularly preferred. The antimony compound preferably contains 50 to 400 ppm, more preferably 100 to 350 ppm, and particularly preferably 150 to 300 ppm of antimony element relative to the generated copolyester resin.

[0039] In addition, as the above-mentioned germanium compound, for example, crystalline germanium dioxide, amorphous germanium dioxide, germanium tetraoxide, germanium hydroxide, germanium oxalate, germanium chloride, tetraethoxygermanium, tetra-n-butoxygermanium, germanium phosphite and the like can be cited. Among them, crystalline germanium dioxide and amorphous germanium dioxide are more preferred, and amorphous germanium dioxide is particularly preferred. These germanium compounds preferably contain 10 to 100 ppm, more preferably 30 to 70 ppm, and particularly preferably 30 to 50 ppm of germanium element relative to the generated copolyester resin.

[0040] In addition, as the titanium compound, for example, tetraalkyl titanates such as tetraethyl titanate, tetraisopropyl titanate, tetra-n-propyl titanate, and tetra-n-butyl titanate and their partial hydrolysis products; titanium oxalate compounds such as titanium acetate, titanium oxalate, ammonium titanium oxalate, sodium titanium oxalate, potassium titanium oxalate, calcium titanium oxalate, and strontium titanium oxalate; titanium trimellitate, titanium sulfate, titanium chloride, hydrolysis products of titanium halides, titanium bromide, titanium fluoride, potassium hexafluorotitanate, ammonium hexafluorotitanate, cobalt hexafluorotitanate, manganese hexafluorotitanate, titanium acetylacetonate, titanium complexes with hydroxy polycarboxylic acids or nitrogen-containing polycarboxylic acids, composite oxides composed of titanium and silicon or zirconium, and reaction products of titanium alkoxides and phosphorus compounds, etc. Among these, tetraisopropyl titanate, tetrabutyl titanate, and potassium titanium oxalate are preferred, and tetrabutyl titanate is particularly preferred. The titanium compound is contained in an amount of preferably 1 to 50 ppm, more preferably 2 to 20 ppm, and particularly preferably 3 to 10 ppm in terms of titanium element, based on the produced copolyester resin.

[0041] As the polycondensation catalyst, aluminum compounds are particularly preferred from the perspective of recyclability (heat resistance, thermal oxidation stability). The aluminum compound is preferably used in combination with a phosphorus compound. As the aluminum compound constituting the polymerization catalyst used in the production of the copolyester resin of the present invention, known aluminum compounds can be used without limitation.

[0042] Specific examples of aluminum compounds include aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, aluminum hydroxychloride, aluminum acetylacetonate, aluminum oxalate, and other organic aluminum compounds and partial hydrolysis products thereof. Among them, carboxylates, inorganic acid salts, and chelates are preferred, among which aluminum acetate, basic aluminum acetate, aluminum lactate, aluminum chloride, aluminum hydroxide, aluminum hydroxychloride, and aluminum acetylacetonate are more preferred, aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, and aluminum hydroxychloride are further preferred, and aluminum acetate and basic aluminum acetate are most preferred.

[0043] The amount of the aluminum compound used in the polymerization catalyst is preferably 15 to 40 ppm, more preferably 17 to 38 ppm, and further preferably 20 to 35 ppm in terms of aluminum atoms relative to the total mass of the obtained polyester resin. When the residual amount of aluminum atoms is less than the above range, the catalyst activity may become poor. On the other hand, when the residual amount of aluminum atoms is greater than the above range, there are cases where the reduction of thermal stability and thermal oxidation stability becomes a problem, and the increase of foreign matter and coloration caused by aluminum becomes a problem. In addition, as described above, even if the aluminum compound is placed under a reduced pressure environment during polyester polymerization, the amount used as a polymerization catalyst remains substantially 100%, so it can be considered that the amount used is the residual amount. In the case where the properties of the copolyester resin can be slightly sacrificed, the content of aluminum atoms in the copolyester resin may also be 9 to 42 ppm.

[0044] The phosphorus compound used in the polymerization catalyst is not particularly limited, but phosphonic acid compounds and phosphinic acid compounds are preferably used because the catalyst activity is significantly improved. Among them, phosphonic acid compounds are preferably used because the catalyst activity is particularly significantly improved.

[0045] Among these phosphorus compounds, when using a phosphorus compound having a phenolic moiety in the same molecule, the improvement of the thermal stability and thermal oxidation stability of the resin is obvious, so it is preferred. As long as it is a phosphorus compound with a phenolic structure, there is no particular limitation. When using one or more compounds selected from phosphonic acid compounds and phosphinic acid compounds having a phenolic moiety in the same molecule, the improvement effect of the catalyst activity and the improvement effect of the thermal stability and thermal oxidation stability of the resin are both obvious, so it is preferred. Among them, when using one or more phosphonic acid compounds having a phenolic moiety in the same molecule, the improvement effect of the catalyst activity and the improvement effect of the thermal stability and thermal oxidation stability of the resin are both particularly obvious, so it is preferred.

[0046] Examples of the phosphorus compound having a phenolic moiety in the same molecule include compounds represented by the following general formulas (1) and (2).

[0047] P(=O)R 1 (OR 2 )(OR 3 ) General formula (1)

[0048] P(=O)R 1 R 4 (OR 2 ) General formula (2)

[0049] (In general formulas (1) to (2), R 1 R represents a hydrocarbon group having 1 to 50 carbon atoms and containing a phenolic moiety, or a hydrocarbon group having 1 to 50 carbon atoms and containing a substituent such as a hydroxyl group, a halogen group, an alkoxy group, or an amino group and a phenolic moiety. 4 R represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms which has a substituent such as a hydroxyl group, a halogen group, an alkoxy group, or an amino group. 2 , R 3 R each independently represents hydrogen, a hydrocarbon group having 1 to 50 carbon atoms, or a hydrocarbon group having 1 to 50 carbon atoms containing a substituent such as a hydroxyl group or an alkoxy group. However, the hydrocarbon group may contain a branched structure, an alicyclic structure such as a cyclohexyl group, or an aromatic ring structure such as a phenyl group or a naphthyl group. 2 and R 4 The ends of the two molecules can be bonded.)

[0050] Examples of the phosphorus compound having a phenolic moiety in the same molecule include p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonic acid, diethyl p-hydroxyphenylphosphonic acid, diphenyl p-hydroxyphenylphosphonic acid, bis(p-hydroxyphenyl)phosphinic acid, methyl bis(p-hydroxyphenyl)phosphinic acid, phenyl bis(p-hydroxyphenyl)phosphinic acid, p-hydroxyphenylphenylphosphinic acid, methyl p-hydroxyphenylphenylphosphinic acid, phenyl p-hydroxyphenylphenylphosphinic acid, p-hydroxyphenylphosphinic acid, methyl p-hydroxyphenylphosphinic acid, and phenyl p-hydroxyphenylphosphinic acid. In addition, examples of the phosphorus compound represented by the following general formula (3) include:

[0051]

[0052] In the general formula (3), X1 and X2 independently represent hydrogen, an alkyl group having 1 to 4 carbon atoms, or a metal having a valency of 1 or more. In addition, the metal of X1 may be divalent or more and X2 may not exist. Furthermore, anions corresponding to the remaining valence of the metal may be arranged on the phosphorus compound. As the metal, Li, Na, K, Ca, Mg and Al are preferred.

[0053] When these phosphorus compounds having a phenolic moiety in the same molecule are added during the polymerization of polyester, the catalytic activity of the aluminum compound is improved, and the thermal stability and thermal oxidation stability of the polyester resin obtained by polymerization are also improved. The reason for this is believed to be that the hindered phenolic moiety in the phosphorus compound improves the thermal stability and thermal oxidation stability of the polyester resin. In this case, when the residual amount of the phosphorus compound is less than 31 ppm, the above-mentioned effect of improving the thermal stability and thermal oxidation stability is weak, and as a result, there is a case where the improvement effect of the thermal stability and thermal oxidation stability of the polyester resin of the present invention and the improvement effect of coloration are not achieved.

[0054] Among the above, the phosphorus compound preferably used as the polycondensation catalyst is at least one phosphorus compound selected from the group consisting of compounds represented by the following chemical formula (4) and chemical formula (5).

[0055]

[0056]

[0057] As the compound represented by the chemical formula (4), Irganox 1222 (manufactured by BASF) is commercially available. Also, as the compound represented by the chemical formula (5), Irganox 1425 (manufactured by BASF) is commercially available, and either may be used.

[0058] The amount of the phosphorus compound used in the polymerization catalyst is preferably 31 to 119 ppm, more preferably 39 to 105 ppm, and further preferably 48 to 92 ppm in terms of phosphorus atoms relative to the total mass of the obtained copolyester resin. When it is less than the above lower limit, the effect of improving thermal stability and thermal oxidation stability may be reduced. On the other hand, when it is greater than the above upper limit, the polymerization activity may be reduced. In addition, as described above, when the phosphorus compound is placed under a reduced pressure environment during the polymerization of the polyester resin, a part of the amount initially added to the system as a catalyst is removed to the outside of the system, and the amount removed is basically a constant ratio, so it is also appropriate to consider the removal ratio and define it as a residual amount. In the case where the characteristics of the copolyester resin can be slightly sacrificed, the content of phosphorus atoms in the copolyester resin can also be 19 to 125 ppm. The thermal stability is preferably 0.7 or less, preferably 0.6 or less, and most preferably 0.5 or less.

[0059] In addition, as described above, the ratio of phosphorus compounds to aluminum compounds is also important in the present invention. Specifically, in the present invention, the molar ratio of phosphorus atoms to aluminum atoms in the polyester resin (P / Al ratio) is preferably greater than 0 and less than 2.6, more preferably 0.2 to 2.4, and further preferably 0.4 to 2.3. Even if the aluminum compound is used alone as a polymerization catalyst, the catalytic activity cannot be fully exerted. In addition to the aluminum compound, the phosphorus compound is also used as a polymerization catalyst and is used in a specific ratio, thereby sufficiently improving the catalytic activity. When the molar ratio of phosphorus atoms to aluminum atoms in the polyester resin is outside the above range, it may not be able to fully exert its function as a polymerization catalyst.

[0060] In the present invention, in addition to the above-mentioned aluminum compound and phosphorus compound, a metal-containing polycondensation catalyst such as a titanium compound, a tin compound, a germanium compound, etc. may be used in combination to further improve the catalytic activity, within the range that the effects of the present invention are not impaired. In this case, the germanium compound is preferably less than 10 ppm in terms of germanium atoms relative to the mass of the obtained polyester resin, the titanium compound is preferably less than 3 ppm in terms of titanium atoms relative to the mass of the obtained polyester resin, and the tin compound is preferably less than 3 ppm in terms of tin atoms relative to the mass of the obtained polyester resin. However, for the purpose of the present invention, it is preferred not to use these metal-containing polycondensation catalysts such as titanium compounds, tin compounds, germanium compounds, etc. as much as possible. In addition, antimony compounds generally used as polymerization catalysts have poor effects on improving the thermal stability and thermal oxidation stability of the above-mentioned resins, and therefore are avoided in the present invention.

[0061] In addition, in the production of the copolyester resin of the present invention, in order to improve the polymerization activity or reduce the acetaldehyde (hereinafter, sometimes referred to as AA) content in the produced copolyester resin to improve the odor (flavor properties), an alkali metal compound and / or an alkaline earth metal compound may be used in combination. AA is a component produced as a by-product during the synthesis of the copolyester resin. Examples of the alkali metal compound and / or alkaline earth metal compound include compounds of lithium, sodium, potassium, rubidium, cesium, francium, calcium, strontium, barium, radium, beryllium, and magnesium, preferably compounds of lithium, sodium, potassium, calcium, and magnesium, more preferably compounds of lithium, sodium, and potassium, and most preferably compounds of lithium and potassium. Specific examples of the alkali metal compound and / or alkaline earth metal compound include carboxylates such as acetates (e.g., lithium acetate), alkoxides, and the like of these elements. These can be added to the reaction system as powders, aqueous solutions, ethylene glycol solutions, and the like. The amount of the alkali metal compound and / or alkaline earth metal compound used is preferably such that the content of the alkali metal element and / or alkaline earth metal element (e.g., lithium element) in the copolyester resin is 1 to 100 ppm, more preferably 1 to 60 ppm, and most preferably 1 to 50 ppm. In addition, this content is a value excluding the content of the sodium element derived from the sodium sulfoisophthalate contained as the dicarboxylic acid component in the copolyester resin of the present invention. When the content of the alkali metal element and / or alkaline earth metal element in the copolyester resin exceeds 100 ppm, the thermal stability tends to decrease. On the other hand, the content of AA in the polyester resin is preferably 150 ppm or less, more preferably 120 ppm, further preferably 110 ppm or less, and most preferably 80 ppm or less. When the content of AA exceeds 150 ppm, the odor tends to decrease.

[0062] In the case of direct esterification, the polycondensation catalyst can be added at any time point from before the start of the esterification reaction or after the end of the pressurized esterification reaction to before the start of the initial polycondensation reaction. When an antimony compound or a titanium compound is used as a polycondensation catalyst, it is preferably added before the esterification reaction. In addition, other polycondensation catalysts, heat stabilizers, and additives are preferably added after the esterification reaction.

[0063] In addition, in the case of the transesterification method, the above-mentioned polycondensation catalyst can be added at any time point from before the start of the transesterification reaction to before the start of the initial polycondensation reaction. The titanium compound not only has the function of a polycondensation catalyst, but also has the function of a transesterification catalyst, so it is preferably added before the start of the transesterification reaction. In addition, other polycondensation catalysts, heat stabilizers, and additives are preferably added after the end of the transesterification reaction. As the transesterification catalyst, titanium compounds such as manganese acetate, magnesium acetate, and titanium tetrabutoxide are preferred. The transesterification catalyst needs to be added before the start of the transesterification reaction.

[0064] In addition, when using a catalyst other than the above-mentioned aluminum compound, a phosphorus compound can be used as a stabilizer. As the phosphorus compound, for example, phosphoric acid, phosphorous acid, phosphonic acid and their derivatives can be listed. As preferred specific examples, phosphoric acid, trimethyl phosphate, tributyl phosphate, triphenyl phosphate, monomethyl phosphate, dimethyl phosphate, monobutyl phosphate, dibutyl phosphate, phosphorous acid, trimethyl phosphite, tributyl phosphite, methylphosphonic acid, dimethyl methylphosphonate, dimethyl ethylphosphonate, dimethyl phenylphosphonate, diethyl phenylphosphonate, diphenyl phenylphosphonate can be listed. Among them, trimethyl phosphate and phosphoric acid are particularly preferred. These phosphorus compounds preferably contain 1 to 100 ppm relative to the generated copolyester, more preferably 3 to 70 ppm, and particularly preferably 5 to 50 ppm.

[0065] In order to improve the color tone of the copolyester resin, a cobalt compound can be added. By adding the cobalt compound, in particular, the color b value can be reduced. The cobalt compound preferably contains 0.5 to 30 ppm, more preferably 1 to 20 ppm, and particularly preferably 1 to 15 ppm in terms of cobalt atoms relative to the copolyester resin. When the content of cobalt atoms is greater than the above range, the copolyester resin becomes black or blue due to the reduction of the cobalt metal, the color L value is less than 50, or the color b value is less than -5, and the commercial value decreases. Examples of the cobalt compound include cobalt acetate, cobalt chloride, cobalt benzoate, cobalt chromate, etc. Among these, cobalt acetate is preferred.

[0066] The copolyester resin obtained by the above-mentioned continuous polycondensation method or batch polycondensation method is usually extracted in the form of strands from an extraction port provided at the bottom of a reaction tank and water-cooled, and then cut into small pieces or sheets.

[0067] The essential feature of the present invention is that the copolyester resin with a low content of free TESD and T2SE3 can be produced by the following methods: a method of simultaneously performing transesterification and esterification; a method of adding a specific diol component during the esterification reaction or transesterification reaction, or after the reaction, to carry out a polycondensation reaction. Among them, the latter method is preferred, that is, a method of adding a specific diol component during the esterification reaction or transesterification reaction, or after the reaction, to carry out a polycondensation reaction. The specific diol component is preferably diethylene glycol or ethylene glycol, and more preferably diethylene glycol. For example, the raw material monomers are first subjected to an esterification reaction or an ester exchange reaction in an amount taking into account the additional amount, and diethylene glycol is added after the reaction, and polycondensation is performed after stirring for 5 minutes or more. The additional diethylene glycol component is preferably 7.5 to 30 mol% of the total diethylene glycol component. In addition, the raw material monomers are first subjected to an esterification reaction or an ester exchange reaction in an amount taking into account the additional amount, diethylene glycol is added during the reaction, and diethylene glycol is further added after further reaction, and polycondensation is performed after stirring for more than 5 minutes. The additional diethylene glycol component is preferably 5 to 20 mol% of the total diethylene glycol component. Furthermore, the raw material monomers are first subjected to an esterification reaction or an ester exchange reaction in an amount taking into account the additional amount, diethylene glycol is added during the reaction, and diethylene glycol is further added after further reaction, and polycondensation is performed after stirring for more than 5 minutes. The additional diol (diethylene glycol + ethylene glycol) component is preferably 7.5 to 30 mol% of the total diol (diethylene glycol + ethylene glycol) component. Furthermore, by subjecting the extracted strands, water-cooled, and then cut into small pieces or flakes to contact with the vapor of diethylene glycol or triethylene glycol for a certain period of time, TESD and T2SE3 can also be reduced. Although the detailed mechanism is unclear, it is believed that the vapor of diethylene glycol or triethylene glycol causes the ring-shaped TESD and T2SE3 to open.

[0068] In the polyester resin composition of the present invention, various additives may be contained as needed within the range that does not damage the characteristics of the present invention. As additives, for example, colorants such as pigments, toners, heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, plasticizers, modifiers, antistatic agents, flame retardants, dyes, etc. may be cited. Titanium oxide and toners are preferred for improving the colorability of the polyester resin composition. The addition amount of titanium oxide is 0 to 20000ppm, preferably 0.1ppm to 15000ppm, and more preferably 0.2ppm to 13000ppm. The addition amount of toner is 0.1ppm to 100ppm, preferably 0.5 to 90ppm, and most preferably 1 to 80ppm. As toners, phthalocyanines and distyrene bisbenzoxazole derivatives may be used. Specifically, it is SOLVAPERM BLUE RLS or PVfastBLUE A4R manufactured by Clariant, Hostalux KS, OB-1 manufactured by Eastman Kodak, etc., and the SOLVAPERM BLUE series manufactured by Clariant, which starts to melt at 250° C. or above and completely melts at about 300° C., is particularly preferred. Since the toner has the same melting point as the polyester itself (230 to 265° C.), it has very good solubility in mixing with polyester, has excellent melting uniformity in a melting machine, and is a material with good spinning operability. Example

[0069] Next, the present invention will be specifically described using examples and comparative examples, but the present invention is not limited to the forms of these examples at all, and appropriate changes can be made within the scope that does not deviate from the gist of the present invention. In addition, the evaluation of the characteristic values ​​in the examples is based on the following methods.

[0070] (1) Composition ratio of copolyester resin About 5 mg of the copolyester resin sample was dissolved in 0.7 ml of a mixed solution of deuterated chloroform and trifluoroacetic acid (volume ratio 9 / 1) and 1 The content of α-H-NMR was determined by H-NMR (Unity 50 manufactured by Varian).

[0071] (2) TESD content 50 mg of the copolyester resin was dissolved in 1 mL of a hexafluoroisopropanol / chloroform mixture (volume ratio = 1 / 9), and further diluted with 4 mL of chloroform. 10 mL of methanol was added thereto to precipitate the polymer, and then centrifuged. The supernatant after centrifugation was concentrated to dryness and then dissolved in 0.4 mL of dimethylformamide. The solution was used to determine the TESD content by high performance liquid chromatography. Device: Waters ACQUITY UPLC Chromatographic column: Waters BEH-C18 2.1×150 mm (manufactured by Waters)

[0072] (3) T2SE3 content The T2SE3 content was measured by high performance liquid chromatography in the same manner as the above-mentioned TESD content measurement.

[0073] (4) Intrinsic viscosity (IV) 0.1 g of a sample dried at 60°C for 24 hours was accurately weighed and dissolved in 25 mL of a mixed solvent of phenol / tetrachloroethane (3 / 2 (mass ratio)), and measured at 30°C using an Ostwald viscometer.

[0074] (5) Number average molecular weight The number average molecular weight was measured by a Waters gel permeation chromatograph using a chloroform / hexafluoroisopropanol mixed solvent (volume ratio = 9 / 1) as a solvent and polystyrene as a test standard. The polystyrene-converted measured value was obtained by using a chloroform / hexafluoroisopropanol mixed solvent (volume ratio = 9 / 1) as an eluent.

[0075] (6) Carboxyl terminal group concentration (AV) Accurately weigh 0.2g of a sample dried at 60°C for 24 hours, and set the weight at this time to W (g). Add 10ml of benzyl alcohol and the weighed sample to a test tube, immerse the test tube in an oil bath heated to 205°C, and stir with a glass rod to dissolve the sample. Set the samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes as A, B, and C. Then, prepare a new test tube, add only benzyl alcohol and treat in the same order, and set the samples with a dissolution time of 3 minutes, 5 minutes, and 7 minutes as a, b, and c respectively. Use a 0.04mol / l potassium hydroxide solution (ethanol solution) with a known factor in advance for titration. Phenolphthalein is used as an indicator, and the end point is when the color changes from yellow-green to light red, and the titration amount (ml) of the potassium hydroxide solution is calculated. Set the titration amount of samples A, B, and C as XA, XB, and XC (ml). Set the titration amount of samples a, b, and c as Xa, Xb, and Xc (ml). Using the titrations XA, XB, and XC at each dissolution time, the titration V (ml) at 0 minutes of dissolution time is calculated by the least square method. Similarly, using Xa, Xb, and Xc, the titration V0 (ml) is calculated. Then, AV is calculated according to the following formula 5. AV(eq / t)=[(V-V0)×NF×1000] / W (Formula 5) NF: Factor of 0.04 mol / l potassium hydroxide solution W: Sample weight (g)

[0076] (7) Hue (color b value and color L value) The color of the copolyester resin sheet was measured using a colorimeter (Model 1001DP, manufactured by Nippon Denshoku Co., Ltd.), and the color b value and color L value were determined.

[0077] (8) Melting point The measurement was performed using a differential scanning calorimeter (DSC) TAS100 thermal analysis system manufactured by TA Instruments. 7.5±0.3 mg of a polyester resin sample was added to an aluminum pan, heated to 280°C using a melting point determination device, maintained for 1 minute, and then rapidly cooled with liquid nitrogen. Then, the sample was heated from room temperature to 300°C at a heating rate of 20°C / min to determine the melting point (Tm) of the sample. Tm is the temperature of the maximum portion of each peak.

[0078] (9) Glass transition temperature (Tg) For a 5 mg sample, a differential scanning calorimeter (model: DSC220) manufactured by Seiko Instruments Inc. was used to raise the temperature from -40°C to 120°C at a heating rate of 10°C / min, and the obtained endothermic curve was obtained. The temperature of the intersection of the extended line of the baseline below the glass transition temperature and the tangent line representing the maximum slope in the transition portion was set as the glass transition temperature (Tg).

[0079] (10) Aluminum atomic content 0.1 g of the sample was dissolved in a 6 M hydrochloric acid solution and allowed to stand for one day, then diluted with pure water to obtain a 1.2 M hydrochloric acid measurement solution. The prepared solution sample was analyzed by inductively coupled high frequency plasma emission spectrometry.

[0080] (11) Phosphorus atomic content For sample 1g, by making its dry ashing decomposition method under the coexistence of sodium carbonate, or by making its wet decomposition method with the mixed solution of sulfuric acid / nitric acid / perchloric acid or the mixed solution of sulfuric acid / hydrogen peroxide, the phosphorus compound is made into orthophosphoric acid. Then, in 1 mol / L sulfuric acid solution, molybdate is reacted to obtain phosphomolybdic acid, which is reduced with hydrazine sulfate to generate heteropoly blue. The absorbance at a wavelength of 830nm is measured by an absorptiophotometer (made by Shimadzu Corporation, UV-150-02). According to the pre-made standard curve, the amount of phosphorus atoms in the sample is quantified.

[0081] (12) Titanium atom content Weigh 1g of sample accurately in a platinum crucible and carbonize and ashed it in an electric furnace. Melt the residue with potassium hydrogen sulfate, dissolve the melt with dilute hydrochloric acid, and determine the content of tetrabutyl titanate (sometimes referred to as TBT) using diantipyrine methane colorimetry. The unit is titanium atoms, expressed in ppm.

[0082] (13) Antimony atomic content 1g of sample was wet decomposed with a mixture of sulfuric acid and hydrogen peroxide. Then, sodium nitrite was added to convert the antimony atoms into Sb 5+ Brilliant green was added to produce a blue complex with antimony. The complex was extracted with toluene and then the absorbance at a wavelength of 625 nm was measured using an absorptiophotometer (manufactured by Shimadzu Corporation, UV-150-02). The amount of antimony atoms in the sample was quantitatively measured colorimetrically based on a pre-made standard curve.

[0083] (14) Cobalt atomic content 1 g of the sample was decomposed by ash in a platinum crucible, and 6 mol / L hydrochloric acid was added to evaporate it to dryness. It was dissolved with 1.2 mol / L hydrochloric acid, and the luminescence intensity was measured using an ICP luminescence analyzer (manufactured by Shimadzu Corporation, ICPS-2000). The amount of cobalt atoms in the sample was quantified based on a pre-made standard curve.

[0084] (15) Lithium atom content Weigh 1g of sample in a platinum crucible and pre-carbonize on a hot plate to 400°C. Then, use an electric furnace FO610 made by YAMATO Science Co., Ltd. to perform ashing treatment at 550°C for 8 hours. After ashing, add a small amount of 6.0N hydrochloric acid and hydrofluoric acid, perform acid decomposition on a hot plate, and heat treatment until the acid is completely volatilized. After the acid decomposition is completed, the lithium element concentration in the determination solution obtained by constant volume using 20mL of 1.2N hydrochloric acid is measured using an inductively coupled high-frequency plasma luminescence analyzer (made by Hitachi High-Technologies Co., Ltd., SPECTROBLUE) to calculate the lithium element content in the sample.

[0085] (16) Mold contamination and foreign matter adhesion The dried copolyester resin sample was put into a sheet extruder and continuously molded for 2 days to a sheet with a thickness of about 0.5 mm. The state of contamination at the die outlet and the state of foreign matter on the sheet surface were visually evaluated according to the following criteria. (Evaluation Criteria) ◎: There is almost no contamination at the die outlet, and the sheet surface is in good condition ○: There is slight contamination at the die outlet, and the sheet surface is in good condition △: There is a small amount of contamination attached to the die outlet and a small amount of foreign matter attached to the sheet surface ×: The mold outlet is seriously contaminated and adhered to, and there are a lot of foreign matter attached to the surface of the sheet

[0086] (17) Haze value The copolyester resin was melted at 280° C. using an injection molding machine (M-150C-DM manufactured by Meiki Seisakusho Co., Ltd.) and molded into a stepped molded plate having a thickness of 2 to 11 mm at a mold temperature of 10° C. The haze value (%) of the 5 mm thick portion of the molded plate was measured using a haze meter (Model NDH2000 manufactured by Nippon Denshoku Co., Ltd.).

[0087] (18)DSC In a YAMATO DP63 dryer, place the sample at 120°C for 120 minutes. For this sample, use a differential scanning calorimeter (DSC) to heat from -100°C to 300°C at 20°C / min, then cool to -100°C at 50°C / min, and then heat from -100°C to 300°C at 20°C / min. Confirm whether a melting peak is displayed during the two heating processes. If no melting peak is displayed in the two heating processes, it is set as "○", and if a melting peak is displayed in any one of them, it is set as "×".

[0088] (19) Thermal stability evaluation: thermal oxidation decomposition parameter (TD) The intrinsic viscosity (IV) of the copolyester resin was measured and taken as IV before the heating test ([IV]i). On the other hand, 3 g of the dried copolyester resin sheet was placed in a glass test tube and immersed in an oil bath at 280° C. for 120 minutes in a nitrogen atmosphere to melt it. The IV after heating was measured ([IV]i). f1 ). By [IV] i and [IV] f1 , TD is calculated according to the following formula. TD=0.245{[IV] f1 -1.47 -[IV] i -1.47} The smaller the value of the thermooxidative decomposition parameter (TD) of the copolyester resin, the higher the thermal stability.

[0089] (20) Acetaldehyde (AA) content in polyester resin: Sample / distilled water = 1 gram / 2cc was added to a nitrogen-substituted glass ampoule, the upper part of the ampoule was sealed, and extraction was performed at 160°C for 2 hours. After cooling, the acetaldehyde content in the extract was measured by high-sensitivity gas chromatography, and the concentration was expressed in ppm. As an odor evaluation, acetaldehyde content of 80 ppm or less was set as ◎, greater than 80 ppm and less than 120 ppm was set as 0, greater than 120 ppm and less than 160 ppm was set as △ to 0, and greater than 160 ppm was set as ×.

[0090] (Example 1) The following slurry is prepared according to the resin composition shown in Table 1, and the slurry contains high-purity terephthalic acid (TPA) and sodium sulfonate dimethyl isophthalate (GCM) as dicarboxylic acid components, and ethylene glycol (EG) and diethylene glycol (DEG) as diol components. Among them, it is adjusted so that the molar ratio (G / A) of all diol components in the slurry relative to the dicarboxylic acid component is 2.2. Then, the slurry is continuously supplied to the first esterification reaction tank in which the reactants have previously remained. Then, under the conditions of stirring, a tank pressure of 0.15MPa, and 257°C, the esterification reaction is carried out in a manner such that the average residence time is 3 hours. The obtained reactant is transferred to the second esterification reaction tank, and the esterification reaction is carried out under the conditions of a tank pressure of 0.05MPa, stirring, and 257°C, so that the average residence time is 1 hour. Then, the obtained esterification reaction product was transferred to a third esterification reaction tank, and an esterification reaction was carried out under stirring, a tank internal pressure of 0.05 MPa, and 257°C.

[0091] Diethylene glycol was added to the generated oligomer in an amount corresponding to 20% of the amount added before the esterification reaction so as to have the target composition, and the mixture was stirred for 15 minutes to allow the reaction.

[0092] To the esterification reaction product, a certain amount of ethylene glycol solution of an aluminum compound (basic aluminum acetate) and an ethylene glycol solution of a phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added as polymerization catalysts, and continuously supplied to the first polycondensation reaction tank, and reacted for 1 hour under stirring at 261°C and 6.7 kPa, and then in the second polycondensation reaction tank, reacted for 1 hour under stirring at 272°C and 0.6 kPa, and further in the final polycondensation reaction tank, polycondensation reaction was carried out for 1 hour under stirring at 275°C and 0.10-0.20 kPa. After the polycondensation reaction, the reactant was passed through a polymer filter, and the molten copolyester resin was extracted from the nozzle of the die in the form of strands, cooled in a cooling bath, and cut into small pieces. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0093] (Examples 2 to 4) Examples 2 to 4 are examples in which the amount of sodium sulfoisophthalate (GCM) was changed. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol, and diethylene glycol was changed to the values ​​of the resin composition shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0094] (Examples 5 and 6) Examples 5 and 6 are examples in which the amount of diethylene glycol (DEG) was changed. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol and diethylene glycol was changed to the values ​​of the resin composition shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0095] (Examples 7 to 9) Examples 7 to 9 are examples in which the number average molecular weight and / or the carboxyl terminal group concentration (AV) were changed. Specifically, the copolyester resin was obtained in the same manner as in Example 1 except that the reaction conditions (average residence time of the esterification reaction) were adjusted so that the number average molecular weight and / or the carboxyl terminal group concentration (AV) were the values ​​shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0096] (Examples 10 to 13) Examples 10 to 13 are examples in which the amount of the aluminum compound and / or phosphorus compound of the polymerization catalyst is changed. Specifically, the copolyester resin is obtained in the same manner as in Example 1 except that the amount of the aluminum compound and / or phosphorus compound added is adjusted so that the amount of the residual aluminum atoms and / or phosphorus atoms is the value shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0097] (Examples 14 to 16) Examples 14 to 16 are examples of further blending lithium acetate in order to improve the odor based on the reduction of the acetaldehyde content in the polymer. Specifically, the following slurry is prepared according to the resin composition shown in Table 1, and the slurry contains high-purity terephthalic acid (TPA) and sodium sulfonate dimethyl isophthalate (GCM) as dicarboxylic acid components, ethylene glycol (EG) and diethylene glycol (DEG) as diol components, and lithium acetate. Among them, it is adjusted so that the molar ratio (G / A) of all diol components in the slurry relative to the dicarboxylic acid component is 2.2. Then, the slurry is continuously supplied to the first esterification reaction tank in which the reactants have remained in advance. Then, the esterification reaction is carried out under the conditions of stirring, a tank pressure of 0.15 MPa, and 257°C, so that the average residence time is 3 hours. The obtained reactant is transferred to the second esterification reaction tank, and the esterification reaction is carried out under the conditions of a tank pressure of 0.05 MPa, stirring, and 257°C, so that the average residence time is 1 hour. Then, the obtained esterification reaction product was transferred to a third esterification reaction tank, and an esterification reaction was carried out under stirring, a tank internal pressure of 0.05 MPa, and 257°C.

[0098] Diethylene glycol was added to the generated oligomer in an amount corresponding to 20% of the amount added before the esterification reaction so as to have the target composition, and the mixture was stirred for 15 minutes to allow the reaction.

[0099] To the esterification reaction product, a certain amount of ethylene glycol solution of an aluminum compound (basic aluminum acetate) and an ethylene glycol solution of a phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added as polymerization catalysts, and continuously supplied to the first polycondensation reaction tank, and reacted for 1 hour under stirring at 261°C and 6.7 kPa, and then in the second polycondensation reaction tank, reacted for 1 hour under stirring at 272°C and 0.6 kPa, and further in the final polycondensation reaction tank, polycondensation reaction was carried out for 1 hour under stirring at 275°C and 0.10-0.20 kPa. After the polycondensation reaction, the reactant was passed through a polymer filter, and the molten copolyester resin was extracted from the nozzle of the die in the form of strands, cooled in a cooling bath, and cut into small pieces. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0100] (Example 17) Example 17 is an example of using antimony compounds and cobalt compounds instead of aluminum compounds as polymerization catalysts. Specifically, the following slurry is prepared according to the resin composition shown in Table 1, and the slurry contains high-purity terephthalic acid (TPA) and sodium sulfonate dimethyl isophthalate (GCM) as dicarboxylic acid components, ethylene glycol (EG) and diethylene glycol (DEG) as diol components. Among them, it is adjusted so that the molar ratio (G / A) of all diol components in the slurry relative to the dicarboxylic acid component is 2.2. Then, the slurry is continuously supplied to the first esterification reaction tank in which the reactants have remained in advance. Then, under the conditions of stirring, tank pressure of 0.15MPa, and 257°C, the esterification reaction is carried out in a manner such that the average residence time is 3 hours. The obtained reactant is transferred to the second esterification reaction tank, and the esterification reaction is carried out under the conditions of tank pressure of 0.05MPa, stirring, and 257°C, the average residence time is 1 hour. Then, the obtained esterification reaction product was transferred to a third esterification reaction tank, and an esterification reaction was carried out under stirring, a tank internal pressure of 0.05 MPa, and 257°C.

[0101] Diethylene glycol was added to the generated oligomer in an amount corresponding to 20% of the amount added before the esterification reaction so as to have the target composition, and the mixture was stirred for 15 minutes to allow the reaction.

[0102] To the esterification reaction product, a certain amount of ethylene glycol solution of an antimony compound (antimony trioxide), an ethylene glycol solution of a cobalt compound (cobalt acetate) and an ethylene glycol solution of a phosphorus compound (Irganox 1222: the compound of the above chemical formula (4)) were added as polymerization catalysts, and continuously supplied to the first polycondensation reaction tank, and reacted for 1 hour under stirring at 261°C and 6.7 kPa, and then in the second polycondensation reaction tank, reacted for 1 hour under stirring at 272°C and 0.6 kPa, and further in the final polycondensation reaction tank, polycondensation reaction was carried out for 1 hour under stirring at 275°C and 0.10-0.20 kPa. After the polycondensation reaction, the reactant was passed through a polymer filter, and the molten copolyester resin was extracted from the nozzle of the die in the form of strands, cooled in a cooling bath, and cut into small pieces. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0103] (Examples 18 and 19) Examples 18 and 19 are examples of using a titanium compound instead of an aluminum compound as a polymerization catalyst. Specifically, the following slurry is prepared according to the resin composition shown in Table 1, and the slurry contains high-purity terephthalic acid (TPA) and sodium sulfonate dimethyl isophthalate (GCM) as dicarboxylic acid components, ethylene glycol (EG) and diethylene glycol (DEG) as diol components, and lithium acetate. Among them, it is adjusted so that the molar ratio (G / A) of all diol components in the slurry relative to the dicarboxylic acid component is 2.2. Then, the slurry is continuously supplied to the first esterification reaction tank in which the reactants have remained in advance. Then, the esterification reaction is carried out under stirring, a tank pressure of 0.15 MPa, and 257°C in a manner such that the average residence time is 3 hours. The obtained reactant is transferred to the second esterification reaction tank, and the esterification reaction is carried out under the conditions of a tank pressure of 0.05 MPa, stirring, and 257°C in a manner such that the average residence time is 1 hour. Then, the obtained esterification reaction product was transferred to a third esterification reaction tank, and an esterification reaction was carried out under stirring, a tank internal pressure of 0.05 MPa, and 257°C.

[0104] Diethylene glycol was added to the generated oligomer in an amount corresponding to 20% of the amount added before the esterification reaction so as to have the target composition, and the mixture was stirred for 15 minutes to allow the reaction.

[0105] A certain amount of 1-butanol solution of tetrabutyl titanate (TBT) and ethylene glycol solution of a phosphorus compound (Irganox 1222: the compound of the chemical formula (4)) were added to the esterification reaction product as a polymerization catalyst, and the mixture was continuously supplied to the first polycondensation reaction tank, and reacted for 1 hour under stirring at 261°C and 6.7 kPa, and then reacted for 1 hour under stirring at 272°C and 0.6 kPa in the second polycondensation reaction tank, and further polycondensed for 1 hour under stirring at 275°C and 0.10-0.20 kPa in the final polycondensation reaction tank. After the polycondensation reaction, the reactant was passed through a polymer filter, and the molten copolyester resin was extracted from the nozzle of the die in the form of strands, and then water-cooled in a cooling bath and cut into small pieces. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0106] (Examples 20 and 21) Examples 20 and 21 are examples in which titanium oxide is further blended to improve colorability. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except for the following conditions: the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol and diethylene glycol, the type and amount of the polymerization catalyst, the carboxyl terminal group concentration (AV) or the number average molecular weight were changed to the values ​​shown in Table 1, lithium acetate was further blended into the slurry, and titanium oxide CR930 (manufactured by Ishihara Sangyo) was added simultaneously with the polymerization catalyst to a concentration of 0.5 ppm (Example 20) or 12000 ppm (Example 21) relative to the polyester resin. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0107] (Examples 22 and 23) Examples 22 and 23 are examples in which a colorant is further blended to improve colorability. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the following conditions were used: the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol, and diethylene glycol, the type and amount of the polymerization catalyst, the carboxyl terminal group concentration (AV), or the number average molecular weight were changed to the values ​​shown in Table 1, and Solvent Blue 45 (manufactured by Clariant) was added as a colorant simultaneously with the polymerization catalyst to a concentration of 0.1 ppm (Example 22) or 50 ppm (Example 23) relative to the polyester resin. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0108] (Comparative Example 1) Comparative Example 1 is an example in which sodium sulfoisophthalate (GCM) is not used as a dicarboxylic acid component and only terephthalic acid is used. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, ethylene glycol and diethylene glycol was changed to the resin composition shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1. In addition, since GCM was not used in Comparative Example 1, the TESD amount and the T2SE3 amount were not measured.

[0109] (Comparative Example 2) Comparative Example 2 is an example in which the amount of sodium sulfoisophthalate (GCM) is too small. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol, and diethylene glycol was changed to the values ​​of the resin composition shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0110] (Comparative Example 3) Comparative Example 3 is an example in which the amount of sodium sulfoisophthalate (GCM) is too large. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol, and diethylene glycol was changed to the values ​​of the resin composition shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0111] (Comparative Example 4) Comparative Example 4 is an example in which the amount of diethylene glycol (DEG) is too large. Specifically, a copolyester resin was obtained in the same manner as in Example 1 except that the blending ratio of terephthalic acid, sulfoisophthalic acid, ethylene glycol, and diethylene glycol was changed to the values ​​of the resin composition shown in Table 1. The evaluation results of the obtained copolyester resin are shown in Table 1.

[0112] [Table 1]

[0113] As can be seen from Table 1, Examples 1 to 23 satisfying all the conditions of the present invention have no mold contamination and foreign matter adhesion, and are excellent in not only transparency (haze value, DSC measurement) but also recyclability (thermal stability). In contrast, Comparative Example 1 does not use sodium sulfoisophthalate (GCM) as a dicarboxylic acid component but uses only terephthalic acid, and the amount of sodium sulfoisophthalate (GCM) in Comparative Example 2 is too small, so the transparency (haze value, DSC measurement) is poor and the recyclability (thermal stability) is poor. In Comparative Example 3, the amount of sodium sulfoisophthalate (GCM) is too large, so the content of cyclic oligomers (TESD, T2SE3) is high, and mold contamination and foreign matter adhesion are high. In Comparative Example 4, the amount of diethylene glycol (DEG) is too large, so the content of cyclic oligomers (TESD) is high, and mold contamination and foreign matter adhesion are high. Industrial Applicability

[0114] The copolyester resin of the present invention has the advantages of transparency and moldability due to the use of diethylene glycol and sodium sulfoisophthalate, and in the continuous production of films, molded products, fibers and other products, mold contamination and foreign matter adhesion to the products are almost non-existent, and resin coloration and molecular weight reduction are also non-existent during recycling. Therefore, the present invention has made a great contribution to the industry.

Claims

1. A copolyester resin, characterized in that: The present invention is a copolymerized polyester resin containing terephthalic acid as a main dicarboxylic acid component and ethylene glycol as a main diol component, wherein, in all polyester resin components, when the total amount of dicarboxylic acid components is 100 mol%, the ratio of terephthalic acid components to all dicarboxylic acid components is 70 to 99.95 mol%, the ratio of sodium sulfoisophthalate to all dicarboxylic acid components is 0.05 to 10 mol%, and when the total amount of diol components is 100 mol%, the ratio of diethylene glycol to all diol components is 1 to 10 mol%, the content of free cyclic monomers composed of terephthalic acid, sodium sulfoisophthalate, ethylene glycol and diethylene glycol is 20 ppm or less, and the content of free cyclic trimers composed of terephthalic acid, sodium sulfoisophthalate and ethylene glycol is 200 ppm or less.

2. The copolyester resin according to claim 1, characterized in that The color b value is -5.0 to 15.

0.

3. The copolyester resin according to claim 1, characterized in that The carboxyl terminal group concentration AV is 3 to 25 eq / t.

4. The copolyester resin according to claim 1, characterized in that The copolyester resin contains aluminum atoms and phosphorus atoms. The content of aluminum atoms in the copolyester resin is 15 to 40 ppm. The molar ratio of phosphorus atoms to aluminum atoms in the copolyester resin is greater than 0 and less than 2.

6.

5. The copolyester resin according to claim 1, characterized in that The copolyester resin further contains alkali metal atoms and / or alkaline earth metal atoms derived from alkali metal compounds and / or alkaline earth metal compounds other than sodium sulfoisophthalate, and the content of the alkali metal atoms and / or alkaline earth metal atoms in the copolyester resin is 1 to 100 ppm.

6. The copolyester resin according to any one of claims 1 to 5, characterized in that The step-shaped molded plate obtained by molding the copolyester resin has a haze value of 10% or less at a thickness of 5 mm.

7. A molded product, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.

8. A heat shrinkable film, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.

9. A fiber, characterized in that Contains the copolyester resin according to any one of claims 1 to 5.

10. A nonwoven fabric, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.

11. An adhesive, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.

12. A coating, characterized in that: Contains the copolyester resin according to any one of claims 1 to 5.